Lignocellulosic Nanocrystals from Sawmill Waste as Biotemplates for Free-Surfactant Synthesis of Photocatalytically Active Porous Silica - El Hajam Maryam; Kandri Noureddine Idrissi; Zerouale Abdelaziz; Wang Xiaoju; Gustafsson Jan; Wang Luyao; Mäkilä Ermei; Hupa Leena; Xu Chunlin (American Chemical Society, 2022)
This work presents a new approach for more effective valorization of sawmill wastes (Beech and Cedar sawdusts), which were used as new sources for the extraction of lignin-containing and lignin-free cellulose II nanocrystals (L-CNCs and CNCs). It was shown that the properties of the extracted nanocrystals depend on the nature of the used sawdust (softwood or hardwood sawdusts). L-CNCs and CNCs derived from Beech fibers were long and thin and also had a higher crystallinity, compared with those obtained from Cedar fibers. Thanks to their interesting characteristics and their high crystallinity, these nanocrystals have been used without changing their surfaces as template cores for nanostructured hollow silica-free-surfactant synthesis for photocatalysis to degrade methylene blue (MB) dye. The synthesis was performed with a simple and efficient sol–gel method using tetraethyl orthosilicate as the silica precursor followed by calcination at 650 °C. The obtained materials were denoted as B/L-CNC/nanoSiO2, B/CNC/nanoSiO2, C/L-CNC/nanoSiO2, and C/CNC/nanoSiO2, when the used L-CNC and CNC cores are from Beech and Cedar, respectively. By comprehensive analysis, it was demonstrated that the nanostructured silica were quite uniform and had a similar morphology as the templates. Also, the pore sizes were closely related to the dimensions of L-CNC and CNC templates, with high specific surface areas. The photocatalytic degradation of MB dye was about 94, 98, 74, and 81% for B/L-CNC/nanoSiO2, B/CNC/nanoSiO2, C/L-CNC/nanoSiO2, and C/CNC/nanoSiO2, respectively. This study provides a simple route to extract L-CNCs and CNCs as organic templates to prepare nanostructured silica. The different silica structures showed excellent photodegradation of MB.